Disease-Modifying Anti-rheumatic Drug Prescription Baihu-Guizhi Decoction Attenuates Rheumatoid Arthritis via Suppressing Toll-Like Receptor 4-mediated NLRP3 Inflammasome Activation - Li, Weijie; Mao, Xia; Wang, Xiaoyue; Liu, Yudong; Wang, Kexin; Li, Congchong; Li, Taixian; Zhang, Yanqiong; Lin, Na (Frontiers in Pharmacology, 2021)
As a traditional Chinese medicine (TCM)-originated disease-modifying anti-rheumatic drug prescription, Baihu-Guizhi decoction (BHGZD) is extensively used for treatment of rheumatoid arthritis (RA) with a satisfying therapeutic efficacy. Mechanically, our previous data indicated that BHGZD may ameliorate RA partially by restoring the balance of "inflammation-immune" system through regulating TLR4-c-Fos-IL2-TNF-alpha axis. TLR4 has been revealed to be involved into the activation of NLRP3 inflammasome complex. Thus, the aim of the current study was to determine the regulatory effects of BHGZD on the TLR4-mediated inflammasome activation during RA progression based on the modified adjuvant-induced arthritis rat model (AIA-M) and the lipopolysaccharide/adenosine triphosphate (LPS/ATP)-induced pyroptosis cellular models. As a result, oral administration of BHGZD exhibited prominent improvement on disease severity of AIA-M rats, such as reducing the redness and swelling of joints, arthritis incidence, arthritic scores and diameter of the limb, and increasing pain thresholds. In line with the in vivo findings, BHGZD treatment effectively inhibited the LPS/ATP-induced pyroptosis of both Raw264.7 macrophage and MH7A cells in vitro by reducing pyroptosis cell death morphology (swollen cells), decreasing propidium iodide (PI) and terminal deoxynucleotidyl transferase-mediated dUTP-fluorescein nick end labeling (TUNEL) positive cells. Notably, the increased expression levels of TLR4, NLRP3, IL-1β, and IL-18 proteins, and the elevated activities of caspase-1 and LDH in vivo and in vitro disease models were markedly reversed by the treatment of BHGZD. In conclusion, the above findings proved the immunomodulatory and anti-inflammatory activities of BHGZD, especially in pyroptosis, which may be attributed to the activation of TLR4-NLRP3 inflammasome signaling.